THE AWARENESS OF VIETNAMESE STUDENTS AND EMPLOYEES TOWARDS THE IMPORTANCE OF ENGLISH - Bilsland; C.; Nagy; H.; Smith; P (International Journal of Psychosocial Rehabilitation, 2020)
Vietnam has been developing and needs a lot of capable human resources. Being fluent in English will be one of the successful keys that helps students to have a bright future after they have graduated from universities. They will have more opportunities to open up great prospects and more competitiveness in a modern society. As a language teacher, how to encourage students to have more motivation to learn English effectively as well as they can recognize the importance of what they need to learn from the language is necessary. This paper was completed thanks to the responses of employees working at Gifu Software Company and FPT University students thanks to the method of investigation developed by Hancock (1998). Research results show that English is positively awared by both employees and students. This study also suggests some solutions for improving English through previous studies.